Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia - Doughty, Paul; Ellis, Ryan J.; Oliver, Paul M. (Zootaxa, 2016)
We provide a taxonomic revision of the genus Crenadactylus, a group of very small clawless geckos from western and central Australia, with currently only one recognized species and four subspecies. Morphological comparisons were made on genotyped specimens from two recent genetic studies, then with an expanded sample to encompass all specimens to determine diagnostic characters in addition to morphological and geographic boundaries. Based on our findings, we           elevate the subspecies Crenadactylus ocellatus ocellatus from south-western Australia and C. o. horni from the Central Uplands to full species. Consultation of the types of Diplodactylus (= Crenadactylus) bilineatus indicate they are                 C. ocellatus based on a dorsal pattern with intermixing of dark and pale scales not shared with any other taxa; we therefore maintain synonymy of ‘D.’ bilineatus with ‘D.’ ocellatus. We describe three new Western Australian species formerly      allocated to C. o. horni: C. occidentalis sp. nov. from the western coast, C. tuberculatus sp. nov. from the Cape Range and C. pilbarensis sp. nov. from the Pilbara region. To stabilize the Kimberley taxa, we also raise C. ocellatus rostralis and C. ocellatus naso, both monophyletic taxa from the monsoonal tropics, to full species, while acknowledging further work is required on the C. naso species complex. All new species treated here possess distinctive morphological characters to diagnose them, including enlarged dorsal tubercles in C. tuberculatus sp. nov., a single enlarged supranasal in C. horni and a single enlarged postmental in C. pilbarensis sp. nov. Pattern was relatively conserved among taxa, with highly  contrasting dark and pale longitudinal lines, with the exception of the type species C. ocellatus that possesses intermixed dark and pale scales and ocelli. Crenadactylus species are separated by deep genetic divergences and are usually allopatrically distributed. This indicates that despite being Australia’s smallest geckos, or possibly because of it, these      diminutive lizards have a long history of localised persistence through major climatic changes over millions of years.